The internationalization of corporate research and development - Christoph Dörrenbächer; Michael Wortmann (Intereconomics, 1991)
Foreign direct investment has grown rapidly in recent decades and, along with it, foreign research and development activities. The following article analyzes the reasons for the internationalization of R&D, examines its patterns in relationship to Germany and discusses the implications for future policy.
Keywords: 330